State of the art of straw treatment technology: challenges and solutions forward - Ma, Yingqun (2022)
Straw as an agricultural byproduct has been recognized as a potential resource. However, open-field straw burning is still the main mean in many regions of the world, which causes the wasting of resource and air pollution. Recently, many technologies have been developed for energy and resource recovery from straw, of which the biological approach has attracted growing interests because of its economically viable and eco-friendly nature. However, pretreatment of straw prior to biological processes is essential, and largely determines the process feasibility, economic viability and environmental sustainability. Thus, this review attempts to offer a critical and holistic analysis of current straw pretreatment technologies and management practices. Specifically, an integrated biological processes coupled with microbial degradation and enzymatic hydrolysis was proposed, and its potential benefits, limitations and challenges associated with future large-scale straw treatment were also elaborated, together with the perspectives and directions forward.